Does Jigsaw Learning Model Matters in Improving Students Achievement? - Hidayati, Annisa Lestari Nur (Classroom Action Research Journal (CARJO), 2019)
This research did the application in High School Brawijaya Smart School Malang with the application the learning model of the jigsaw. The subject of this research is to grade X cross-interest. This research aims to find out how the jigsaw learning model implementation in class X cross-interest in economics subject in high school BSS and up to know how focused learning jigsaw to increase student learning outcomes grade X cross-interest High School BSS Malang. This study used a qualitative approach. This type of research is the research action class implemented in 2 cycles. The data used in this research is the primary data obtained from the learning activities of students. This research data gathering techniques using interview techniques, observation sheets, test better, and documentation. The result of this study demonstrate the application of the learning model of jigsaw has been applied very well and was able to increase the learning outcomes of student of class X cross-interest which has been evidenced by the increase in average yield learning activities post-test in cycle I of â€œ62,14â€ rise in cycle II of â€œ85,35â€. Based on the result of research conducted, the advice that can be give is 1) is expected to implement the BSS model high school teacher learning jigsaw is not only on the material system of payment and means of payment, but for other materials that have the same problem 2) expected for the next researcher can measure student learning outcomes in the affective and psychomotor domains.Â Keywords:Â Jigsaw learning models, learning outcomes, students' activity